Analysis of Employee Workload Using the Workload Analysis (WLA) Method (Case Study at Production Department 1A of PT XYZ) - Suherman, Rizkia Lucyani; Safariyani, Eva; Siagian, Nabila Pritia Rizqika (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
Industrial development in Indonesia highly depends on human resources as the primary element to ensure operational continuity and efficiency. This study analyzes the workload of employees using the Workload Analysis (WLA) method to determine the optimal number of workers in the Production Department 1A of PT XYZ. Data used in this research include production realization, shift distribution, and downtime records throughout 2024. The WLA method was applied systematically through stages of productivity calculation, uniformity test, data adequacy test, standard time calculation, and workload ratio assessment. The findings indicate that the employees’ workload ratio reached 94.44%, meaning most of the employees’ working capacity was efficiently utilized without exceeding the maximum limit. The optimal number of workers required for the department is eight people per group, which matches the actual workforce in the field. Although the production performance decreased between August and October, it was primarily caused by equipment downtime rather than excessive workload. These results highlight that the workforce distribution and performance at PT XYZ remain within efficient and acceptable operational standards. Keywords: Workload Analysis, Employee Efficiency, Human Resource Planning, Productivity, Industrial Operations.